ORGANIZATIONAL CHANGE, ENVIRONMENTAL CHANGE AND CHANGE IN MANAGEMENT ACCOUNTING PRACTICES: A CONTINGENCY APPROACH - Nanik Wahyuni; Novi Lailiyul Wafiroh; Boge Triatmanto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
In this study, the impact of mediated organizational changes and environmental changes on management accounting procedures is investigated. The management of the organization will need to make administrative and management accounting practice adjustments due to the high level of environmental unpredictability. This study employs a survey approach with 149 company managers in mid-to-high level positions in East Javan manufacturing companies as respondents. Data analysis techniques using Smart PLS are used to examine the relationship between changes in the environment and changes in management accounting practices, both directly and indirectly. The findings demonstrated that modifications in management accounting procedures are positively and strongly impacted by ecological changes. Changes in management accounting procedures benefit from organizational changes. On the other hand, modifications to the practice of management accounting cannot be mediated by changes to the organization. This study is unique in that it examines how environmental changes impact management accounting practices. Specifically, it shows that changes in technology and a highly competitive market will impact management accounting methods related to evaluation, costing, and decision-making. Changes in the organization's structure and technology utilization support this shift in management accounting.